THE RELATIONSHIP OF SMOKING HABITS WITH HBA1C LEVELS IN TYPE TWO DM PATIENTS AT GOTONG ROYONG HOSPITAL - Valencia Dewangker, Audrey Jesie; Muliono, Ari Christy; Hendrata, Adi Pramono (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background: Diabetes Mellitus (DM) is a disease whose prevalence continues to increase every year. In 2019, Indonesia was ranked number 7 with the highest number of DM sufferers, namely 10.7 million. Diabetes mellitus is a chronic metabolic disease characterized by increased blood glucose levels, this occurs because there is not enough insulin produced by the pancreas or a condition where the body cannot use the insulin produced effectively. One examination that can be used to assess a patient's glycemic control is the Glycated Hemoglobin (HbA1c) examination. Smoking habit is known to be a risk factor for diabetes mellitus. Even though there are many disadvantages, the number of smokers in Indonesia is still difficult to reduce due to the lack of education and control regulations that suppress smoking behavior in society. This causes smoking to become a risk factor for many uncontrolled diseases in the world of health.Objective: The aim of this study was to analyze the relationship between smoking habits and HbA1c levels in male patients with type two DM at the Gotong Royong Hospital.Research method: This research uses observational analytical research with a case control study approach. In the research sample, namely type two Diabetes Mellitus patients who had their HbA1c levels checked at the Gotong Royong Hospital, a questionnaire was completed regarding the patient's smoking habits. From the results of the questionnaire, patients will be classified into non-smokers, light smokers, moderate smokers, and heavy smokers.Result: There is no significant relationship between smoking habits and HbA1c levels in type two diabetes mellitus patients at Gotong Royong Hospital with a P-value = 0.681.